(untitled) (Damu Journal of Sport Sciences, 2024)
The sport of track and field is classified among the games that require high physical abilities, as these competitions, especially speed races, require physical abilities to a large extent to decide the achievement. The research aims to standardize the training load for special endurance (phosphogyne and lactic speed endurance) and (strength endurance) as the most influential elements in the achievement using modern devices and harnessing artificial intelligence in controlling the training loads for these elements using the (COOSPO) (GPS) device and linking them in the difficulty equation with the Excel program (EXELL) to find the immediate training loads for the competitors. It is one of the modern technical devices for monitoring the load for advanced 400m runners The researchers used the experimental method by designing the control and experimental groups with pre- and post-measurements to suit the nature of the research. The research community represents the 200m event competitors of the clubs actually participating in the Iraqi Clubs Championship for the season (2022-2023) in the Middle Euphrates Governorates. The researchers used the program by determining the maximum intensity for each physical element (speed endurance and strength endurance) according to the maximum pulse by the researchers. The researchers entered the intensity for each element that is appropriate and suitable for training and entered the upper limits that should not be reached within the (coospo) program, as well as determining the minimum limits of the pulse that should not be reached in order for the training to be effective. When the player exceeds these limits, this exceedance will be announced by the program and then to the device. The researchers concluded: Training according to artificial intelligence technology significantly developed some elements of special physical fitness, special endurance and achievement among advanced 200m runners. _ Whereas the training load was accurately standardized using artificial intelligence technology and showed a noticeable improvement in the variables under study, the elements of physical fitness, special endurance and special endurance among advanced 200m runners. _ The technique of standardizing physical load was developed using artificial intelligence technology for the experimental group, and there was a clear difference between the pre- and post-measurement of the experimental group, in favor of the post-measurement.